Physicochemical analysis of hot water springs of Sikkim-Polok Tatopani, Borong Tatopani and Reshi Tatopani - Sherpa, Mingma Thundu; Das, Sayak; Thakur, Nagendra (Recent Research in Science and Technology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]–> Fenced by the geo-political features all around, Sikkim sits magnificently in the lap of The Himalayas with Mount Khanchengdzonga signifying the peaks of divinity and cultural proximity. Sikkim is the natural ecological host to many Hot springs of geothermal characteristics. Hot Springs of Sikkim are regarded as ethical and holistic elements having importance of locale panacea. Hot springs are any natural geothermal spring or a natural discharge of groundwater with elevated temperature with respect to the surrounding. The characteristics or the suitability of these hot springs for human use is determined by its chemical constituents. Most of the Hot Springs is rich in several kinds of chemicals and minerals. Presence of these chemicals and minerals along with higher temperature of these hot springs determine its balneotherapeutic properties. The average temperature of the studied Hot springs being 60°C according to Kent classification as “Scalding” can be regarded as the best ecological niche for thermophilic microorganisms. These Hot springs are supposed to cure off many bone related diseases like arthritis and is also equivalently used in treatment of skin infections and diseases. For curing the Gastrointestinal and bowel associated diseases, water from these hot springs is also drunk. Hence a complete detailed study of the chemicals and the physical properties of the three Hot springs of Sikkim were studied. 30 different physicochemical parameters of the water samples collected from these study areas were analyzed using the ICPMS Spectroscopic methods and Kit method. Physical properties like colour, conductivity, turbidity etc. and chemical parameters like the quantification of anions, cations, trace elements and other chemical constituents of the Tatopani were analysed. A comparison with W.H.O. standards showed that the water sample of Polok and Borong Tatopani water is suitable for drinking purposes whereas Reshi Tatopani water showed higher concentration of TDS (i.e. 608mg/l).